Clinical impact of continuous nursing under IMB mode combined with nutrition intervention on body composition, nutritional indicators, and negative emotions of patients undergoing metabolic bariatric surgery - Zhou, Lingling; Xia, Yuan; Qiu, Yanyu; Yao, Yangyang; Wu, Jinsheng; Ji, Guangnian; Liu, Cui (Frontiers in Surgery, 2025)
AimThe research aimed to elucidate application impact of continuous nursing under IMB mode combined with nutrition intervention on patients after metabolic bariatric surgery (MBS).MethodsEighty obese patients who underwent MBS in our hospital from January 2021 to January 2023 were divided into a control group (CG, n = 40) and an experimental group (EG, n = 40). The CG received conventional continuous nursing, while the EG received continuous nursing under the IMB mode combined with nutrition intervention. Body composition, biochemical indicators, and negative emotion scores were compared between the two groups before and after surgery.ResultsOne month and three months after surgery, weight, fat-free mass, muscle mass, fat mass, visceral fat area, and total cellular water content in both groups demonstrated depletion relative to those before surgery (P < 0.05), whereas fat-free mass and muscle mass in EG demonstrated elevation relative to those in CG during the same period (P < 0.05), and no statistical significance in weight, fat mass (FM), visceral fat area, and total cellular water content demonstrated between both groups during the same period (P > 0.05); C-reactive protein (CRP), and glycated hemoglobin (HbA1c), levels in both groups demonstrated depletion relative to those before surgery (P < 0.05), and CRP and HbA1c levels in EG demonstrated depletion relative to those in CG during the same period (P < 0.05); serum albumin (ALB), prealbumin (PA), vitamin A, vitamin B1, vitamin B2, vitamin B6, vitamin C, and ferritin levels in both groups demonstrated depletion relative to those before surgery (P < 0.05), whereas ALB, PA, vitamin A, vitamin B1, vitamin B2, vitamin B6, vitamin C, and ferritin levels in EG demonstrated elevation relative to those in CG during the same period (P < 0.05); Hamilton Anxiety Scale (HAMA) and Hamilton Depression Scale (HAMD) scores in both groups demonstrated depletion relative to those before surgery, and HAMA and HAMD scores in EG demonstrated depletion relative to those in CG during the same period (P < 0.05).ConclusionCombining IMB-based continuous nursing and nutrition intervention reduces post-MBS anxiety and depression, preserves muscle mass, improves nutritional status, and enhances public acceptance of MBS, promoting its advancement.